Synthesis, Characterization and Theoretical Study of 1,2(2,2-dihydroxy benzelidenamine) Phenyl Complexes - Najeeb, Dina A; Ahmed, Ahmed; Yusop, Muhammad Rahimi (Al-Nahrain Journal of Science, 2017)
New schiff base and its metal complexes of Co(II), Ni(II), Fe(II) and Cu(II) has been synthesized from O-phenylenediamine and O-hydroxyl benzaldehyde. The ligand and its complexes were described the distinctive nature of element by elemental analysis (C,H,N), FTIR, UV-Vis, and magnetic susceptibility. Hyperchem-7 software was used in this project for a theoretical treatment of the synthesized complexes under gas phase condition. PM3 method was used to calculate: heat of formation (ΔHfە), binding energy (ΔEb) and total energy (ΔET) for both ligand and its complexes at 298 K. Additionally, the electrostatic potential of the free ligand (L) was calculated to see the active sites of the product complexes. According to the results of this research, the produced complexes form [ML] type composition where L ligand=1,2(2,2-dihydroxy benzeliden amine). Phenyl and M=Co, Ni, Fe and Cu.